2018
DOI: 10.1016/j.palaeo.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic redox conditions through the late Pliensbachian to early Toarcian on the northwestern Panthalassa margin: Insights from pyrite and geochemical data

Abstract: The early Toarcian oceanic anoxic event (T-OAE; ~183 Ma) was a significant palaeoenvironmental perturbation associated with marked changes in oceanic redox conditions. However, the precise redox conditions and redox history of various water masses during the T-OAE, especially those from outside the Boreal and Tethyan realms, are unclear. To address this issue, we present pyrite framboid data from an upper Pliensbachian to lower Toarcian succession deposited on the NW Panthalassic margin in a shallow-water sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…4), though these are low values if compared with central and northern European outcrops. Thus, for the Serpentinum Zone (Levisoni Zone for Mediterranean biozonation and Falciferum Zone for sub-boreal biozonation), the TOC values range from 5 % to 15 % in the outcrops of northern Europe (Saelen et al, 2000;Röhl et al, 2001;Bucefalo-Palliani et al, 2002;Mailliot et al, 2006;McArthur et al, 2008;Baroni et al, 2018;Thibault et al, 2018;Fantasia et al, 2019;among others), whereas in the Tethys region (southern Europe and North Africa) the values range from 0.5 % to 3 % (Jenkyns, 1985(Jenkyns, , 1988Jenkyns et al, 2002;Hesselbo et al, 2007;Bodin et al, 2010;Reolid et al, 2012b;Rodrigues et al, 2019;Ruebsam et al, 2020a, b;among others). This stands as evidence of the geographic variations of the T-OAE signal (see also Hermoso et al, 2009;Ruebsam et al, 2020b).…”
Section: Organic Matter and Sea Bottom Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…4), though these are low values if compared with central and northern European outcrops. Thus, for the Serpentinum Zone (Levisoni Zone for Mediterranean biozonation and Falciferum Zone for sub-boreal biozonation), the TOC values range from 5 % to 15 % in the outcrops of northern Europe (Saelen et al, 2000;Röhl et al, 2001;Bucefalo-Palliani et al, 2002;Mailliot et al, 2006;McArthur et al, 2008;Baroni et al, 2018;Thibault et al, 2018;Fantasia et al, 2019;among others), whereas in the Tethys region (southern Europe and North Africa) the values range from 0.5 % to 3 % (Jenkyns, 1985(Jenkyns, , 1988Jenkyns et al, 2002;Hesselbo et al, 2007;Bodin et al, 2010;Reolid et al, 2012b;Rodrigues et al, 2019;Ruebsam et al, 2020a, b;among others). This stands as evidence of the geographic variations of the T-OAE signal (see also Hermoso et al, 2009;Ruebsam et al, 2020b).…”
Section: Organic Matter and Sea Bottom Oxygenationmentioning
confidence: 99%
“…Oxygen-depleted conditions in marine ecosystems in some areas reached generalized anoxia and euxinia (e.g. Gill et al, 2011;Izumi et al, 2018;Ruebsam et al, 2018;Suan et al, 2018) but did not affect all basins and palaeomargins alike (e.g. Boomer et al, 2009;Reolid et al, 2014aReolid et al, , 2015McArthur, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Organic carbon isotope data for 13 of the samples measured for Re-Os analysis had previously been published in Izumi et al (2012Izumi et al ( , 2018aIzumi et al ( , 2018b and Kemp and Izumi (2014) (data are identified as such in Table S1). The remaining 11 samples were measured for d 13 Corg in this study.…”
Section: Organic Carbon-isotope (D 13 Corg) Analysismentioning
confidence: 99%
“…Litho‐ and carbon‐isotope stratigraphy of the Sakuraguchi‐dani section, with the stratigraphical horizon of the analysed sandstone sample shown. Log is modified after Izumi, Kemp, et al () and Izumi, Endo, et al (); carbon isotope data are from Izumi, Kemp, et al () and Izumi, Endo, et al (); and biostratigraphical framework is based on Nakada and Matsuoka (). Shaded intervals represent the main and recovery phases of negative carbon‐isotope excursion characterizing the early Toarcian oceanic anoxic event.…”
Section: Geological Settingmentioning
confidence: 99%
“…Understanding of palaeoenvironmental changes during the T‐OAE has mainly been based on studies of European successions, where deposition occurred in the Tethyan and Boreal realms (Bailey, Rosenthal, McArthur, van de Schootbrugge, & Thirlwall, ; Hesselbo et al, ; Hesselbo, Jenkyns, Duarte, & Oliveira, ; Kemp, Coe, Cohen, & Schwark, ; Mattioli, Pittet, Petitpierre, & Mailliot, ; Suan, van de Schootbrugge, Adatte, Fiebig, & Oschmann, ). The Nishinakayama Formation of the Toyora Group, southwest Japan (Figure ), provides a rare example of a record of the T‐OAE outside this area and is also one of the most expanded records of the event yet described (Izumi, Endo, Kemp, & Inui, ; Izumi, Kemp, Itamiya, & Inui, ; Izumi, Miyaji, & Tanabe, ; Kemp & Izumi, ). The sedimentary basins of the Japanese Lower Jurassic shallow‐marine strata, including the basin where the Nishinakayama Formation was deposited (Toyora sedimentary basin), are interpreted to have been located at the north‐western marginal area of the Panthalassa Ocean (Dera et al, ; Golonka, ; Jenkyns, ; Figure ).…”
Section: Introductionmentioning
confidence: 99%